PENDIDIKAN INKLUSI (ANAK BERKEBUTUHAN KHUSUS) PERSPEKTIF ILMU PENDIIDKAN ISLAM - SARIMA, ANDI - (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study discusses inclusive education in the perspective of Islamic education science. There are two main objectives achieved in this research, namely first, explaining inclusive education in the view of Islamic education; second, to reveal the supporting and inhibiting factors of inclusive education. In achieving these goals, researchers used qualitative methods with a library research approach. The results of this study explain that inclusive education in the view of Islamic education emphasizes the importance of education without differentiating humans, because every human being is obliged to study whether male, female, disabled or normal. Inclusive education instills the value of social education in students, both children with special needs and non-special needs children from an early age, so that in inclusive education one child respects one another and eliminates discriminatory attitudes. Therefore, the supporting factors for inclusive education are government concern, stakeholder involvement in providing education, concern for the business world, school policies and supportive parents, while the inhibiting factors for inclusive education are lack of knowledge of handling children with special needs, because teachers are not from special education. In general, teachers in elementary schools come from elementary school teacher education study programs, so they have limited information regarding the specific handling of children with special needs. In addition, the inhibiting factor in the implementation of inclusive education programs is a curriculum that has not been oriented towards being prepared for inclusive school programs, so that this becomes a particular difficulty for educators